Bone Resorption Is Regulated by Circadian Clock in Osteoblasts. (3rd March 2017) - Takarada, Takeshi; Xu, Cheng; Ochi, Hiroki; Nakazato, Ryota; Yamada, Daisuke; Nakamura, Saki; Kodama, Ayumi; Shimba, Shigeki; Mieda, Michihiro; Fukasawa, Kazuya; Ozaki, Kakeru; Iezaki, Takashi; et al.
ABSTRACT: We have previously shown that endochondral ossification is finely regulated by the Clock system expressed in chondrocytes during postnatal skeletogenesis. Here we show a sophisticated modulation of bone resorption and bone mass by the Clock system through its expression in bone‐forming osteoblasts. Brain and muscle aryl hydrocarbon receptor nuclear translocator‐like protein 1 ( Bmal1 ) and Period1 (Per1) were expressed with oscillatory rhythmicity in the bone in vivo, and circadian rhythm was also observed in cultured osteoblasts of Per1::luciferase transgenic mice. Global deletion of murine Bmal1, a core component of the Clock system, led to a low bone mass, associated with increased bone resorption. This phenotype was recapitulated by the deletion of Bmal1 in osteoblasts alone. Co‐culture experiments revealed that Bmal1 ‐deficient osteoblasts have a higher ability to support osteoclastogenesis. Moreover, 1α, 25‐dihydroxyvitamin D3 [1, 25(OH)2 D3 ]‐induced receptor activator of nuclear factor κB ligand ( Rankl ) expression was more strongly enhanced in both Bmal1 ‐deficient bone and cultured osteoblasts, whereas overexpression of Bmal1 /Clock conversely inhibited it in osteoblasts. These results suggest that bone resorption and bone mass are regulated at a sophisticated level by osteoblastic Clock system through a mechanism relevant to the modulation of 1, 25(OH)2 D3 ‐induced Rankl expression in osteoblasts. © 2017 American Society for Bone and Mineral Research.